Early Protein Intake Influences Neonatal Brain Measurements in Preterms: An Observational Study - Terrin, Gianluca; De Nardo, Maria Chiara; Boscarino, Giovanni; Di Chiara, Maria; Cellitti, Raffaella; Ciccarelli, Simona; Gasparini, Corinna; Parisi, Pasquale; Urna, Matteo; Ronchi, Benedetta; Russo, Alessia; Sabatini, Giulia; et al. (Frontiers in Neurology, 2020)
Introduction: To limit extrauterine growth restriction (EUGR), recent guidelines on nutrition of preterm neonates recommended high protein intake since the first day of life (DOL). The impact of this nutritional strategy on the brain is still controversial. We aimed to evaluate the effects of protein intake on early cerebral growth in very low birth weight (VLBW) newborns. Materials and methods: We performed serial cranial Ultrasound (cUS) scans at 3-7 DOL and at 28 DOL in VLBW consecutively observed in Neonatal Intensive Care Unit (NICU). We analyzed the relation between protein intake and cerebral measurements at 28 DOL performed by cUS. Results. We enrolled 100 newborns (GA 29 ± 2 weeks; BW 1274 ± 363 g). A significant (p<0.05) positive correlation between enteral protein intake and bi-parietal diameter (r 0.490**), occipital-frontal diameter (r 0.608**), corpus callosum (length r 0.293*, genu r 0.301*), caudate head (right r 0.528**, left r 0.364**), cerebellum (transverse diameter r 0.440**, vermis height r 0.356**, vermis width r 0.377**) were observed at 28 DOL. Conversely, we found a significant negative correlation of protein intake given by parenteral nutrition (PN) with bi-parietal diameter (r -0.524**), occipital-frontal diameter (r -0.568**), body of corpus callosum (r -0.276*), caudate head (right r -0.613**, left r -0.444**), cerebellum (transverse diameter r -0.403**, vermis height r -0.274*, vermis width r -0.462**) at 28 DOL. Multivariate regression analysis showed that measurements of occipital-frontal diameter, caudate head and cerebellar vermis at 28 DOL depend positively on protein enteral intake (r 402*, r 0.305* and r 0.271*) and negatively by protein parenteral intake (r -0.278*, r -0.488* and r -0.342*). Conclusion. Brain development in neonatal life depends on early protein intake. High protein intake affects cerebral structures’ measurements of preterm newborn when administered by PN. Positive impact on brain development encourages the administration of recommended protein intake mainly by enteral nutrition (EN).